Fornecimento relativo de irrigação como estratégia de gestão para sustentabilidade do distrito de irrigação baixo acaraú - Beltrão Júnior, José Aguiar (2017)
The objective of this research was to use the Irrigation Relative Supply (FRI) indicator of the S@I system as a strategy for the analysis of performance indicators of the Irrigation District with a view to the water and economic sustainability of the Low Acaraú Irrigated Perimeter. This Perimeter is located on the northern coast of the State of Ceará, where a model of Irrigation Advisory Service (SAI) has been developed through a pioneering project carried out by the Institute of Innovation in Irrigated Agriculture (Inovagri). The SAI developed in the Low Acaraú is made up of a field team and web service software (Web Service) with daily information to irrigators (via SMS and / or e-mail) of the irrigation time in each sector of the lots Defined on the basis of the climatological water balance methodology. The FRI lists the amount of water used in the lot with the defendant through the irrigation recommendation provided by the advisory service to the irrigant. For the calculation of the FRI, was selected the period from August to November of the years 2012, 2013 and 2014, in lots of small farmers cultivated with the main crops of the Irrigated Perimeter: coconut, banana and guava. For the evaluation of the development of the Low Acaraú Irrigation District (Dibau) were collected data on the gross value of production, revenue generation, Operation and Maintenance costs, as well as areas delivered, cultivated, irrigated and harvested from the Irrigation Perimeter were collected for the period from 2012 to 2014. The FRI Presented an annual decline reflecting the cumulative effects of water scarcity on the Low Acaraú Irrigated Perimeter, despite the economic point of view an evolution in the management of the Low Acaraú Irrigation District. Despite the evolution in the Financial Efficiency indicator, the District still lacks administrative adjustments to achieve its self-sustainability, due to the high cost of O & M, the increase in cost for Dibau to maintain One Hectare in production, in addition to the default rate of Tariff K2 be considered very high. The increase in water productivity and the increase in product prices contributed positively. The Irrigation Relative Supply indicator of the S@I system assisted in the management of Dibau in order to identify farmers who use water without technical principles, in excess or deficit, a fact that harms crop development, negatively reflecting the District's financial performance. The use of the FRI in 2014 was important in the administration of the Irrigation District, helping in decision making and allowing a balance in management in the midst of the water crisis.